Platelet-rich plasma, bone marrow and chitosan in minimally invasive plate osteosynthesis of canine tibia fractures - a randomized study - Fernandes Filgueira, Fabricia Geovania; Minto, Bruno Watanabe [UNESP]; Chung, Denise Granato [UNESP]; Prada, Tiago Carmagni [UNESP]; Rosa-Ballaben, Natalie Massaro [UNESP]; Nogueira Campos, Maria Gabriela (Czech Academy Agricultural Sciences, 2019)
The goal of this study was to analyse the effects of percutaneous application of platelet rich plasma (PRP), autologous bone marrow concentrate (BM) and chitosan gel (CHI) on bone consolidation following minimally invasive plate osteosynthesis (MIPO) of the fractures of the tibia in dogs. Client-owned dogs (n = 30) with tibial fracture were divided into four treatment groups - Group 1 (control), Group 2 (BM), Group 3 (PRP) and Group 4 (CHI). The biomaterial specific to each group was injected at the fracture site immediately after the MIPO procedure. Serial radiographs were used to determine the fracture line and the development of periosteal callus immediately after surgery and at 15, 30, 60, 90 and 120 days post-surgery. There was no significant difference (P > 0.05) in the degree of oedema or grade of lameness between the groups. Grade 4 (minimum) or 5 lameness (absent) was observed in 70% of animals from all groups at 15 days post-surgery. The biomaterials PRP, BM and CHI combined with MIPO contribute to bone consolidation of tibial fractures in dogs and do not cause adverse reactions or fracture complications. Bone marrow concentrate results in shorter bone consolidation time.
Keywords: bone consolidation; surgery; biomaterials; dogs; percutaneous application